E/e’ Ratio in Patients with Unexplained Dyspnea: Lack of Accuracy in Estimating Left Ventricular Filling Pressure - Santos, Mário (Circ Heart Fail, 2015)
BACKGROUND: Elevated left ventricular filling pressure (LVFP) is a cardinal feature of heart failure with preserved ejection fraction (HFpEF). Mitral E/e’ ratio has been proposed as a non-invasive measure of LVFP. We studied the accuracy of E/e’ to estimate and track changes of LVFP in patients with unexplained dyspnea. METHODS AND RESULTS: We performed supine and upright transthoracic echocardiography in 118 patients with unexplained dyspnea who underwent right heart catheterization. Supine E/e’ ratio modestly but significantly correlated with supine pulmonary arterial wedge pressure (PAWP) (r=0.36; p<0.001) and demonstrated poor agreement with PAWP values (Bland-Altman limits of agreement of −8.3 to 8.3 mmHg; range: 6.5 to 21.2 mmHg). Similarly, E/e’ ratio cut-off of 13 performed poorly in identifying patients with elevated LVFP (sensitivity 6%, specificity 90%). The ROC area of E/e’ was 0.65 (95% CI: 0.50-0.79). With change from the supine to upright position, PAWP decreased (−5±4 mmHg; p<0.001) as did both E-wave (−17±15 cm/s; p<0.001) and e’ (−2.7±2.7 cm/s; p<0.001) velocities, while E/e’ remained stable (+0.2±2.6; p=0.57). Positional change in PAWP correlated modestly with change in E-wave (r=0.37; p<0.001) velocity. There was no appreciable relationship between change in PAWP and change in average E/e’ (r=−0.04; p=0.77) and in half the patients the change in PAWP and E/e’ were directionally opposite. CONCLUSIONS: In patients with unexplained dyspnea, E/e’ ratio neither accurately estimates PAWP nor identifies patients with elevated PAWP consistent with HFpEF. Positional changes in E/e’ ratio do not reflect changes in PAWP.